2021
DOI: 10.3389/fpls.2021.711853
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biochemical Insights Into Early Responses of Hemp to Cd and Zn Exposure and the Potential Effect of Si on Stress Response

Abstract: With the intensification of human activities, plants are more frequently exposed to heavy metals (HM). Zinc (Zn) and cadmium (Cd) are frequently and simultaneously found in contaminated soils, including agronomic soils contaminated by the atmospheric fallout near smelters. The fiber crop Cannabis sativa L. is a suitable alternative to food crops for crop cultivation on these soils. In this study, Cd (20 μM) and Zn (100 μM) were shown to induce comparable growth inhibition in C. sativa. To devise agricultural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 78 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…A strengthening action of Pseudomonas sp. SVB-B33 on secondary cell wall of hemp roots is to be expected since previous studies reported the ability of C. sativa to take up silicon (Si, as silicic acid), deposit it as silica in the cell wall [12,50] and respond better to abiotic stresses in the presence of the metalloid [51,52].…”
Section: Discussionmentioning
confidence: 93%
“…A strengthening action of Pseudomonas sp. SVB-B33 on secondary cell wall of hemp roots is to be expected since previous studies reported the ability of C. sativa to take up silicon (Si, as silicic acid), deposit it as silica in the cell wall [12,50] and respond better to abiotic stresses in the presence of the metalloid [51,52].…”
Section: Discussionmentioning
confidence: 93%
“…Certain metals have the ability to function as catalysts, hence, potentially expediting the carbonation process of lime. Conversely, these metals could also act as inhibitors [25][26][27].…”
Section: Understanding Hempcretementioning
confidence: 99%
“…This land has to be remediated before re‐using for food production to protect human health and the environment. Previous works have demonstrated that several non‐food industrial crops have the ability to accumulate HM&M in their aerial biomass contributing to the removal of the toxic elements from the soil (Barbosa et al, 2016; Fernando et al, 2016; Galić et al, 2019; Guo et al, 2019; Luyckx et al, 2021; Nsanganwimana et al, 2014; Witters et al, 2009).…”
Section: Introductionmentioning
confidence: 99%